Detection and Analysis of Activity Recognition for Hand Rehabilitation - Hamzah, Ahmad; Nurul Atikah , Mohd Nor (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper deals with detection and analysis of hand activity recognition for rehabilitation purposes. The research attempts to analyze human hand movements analysis based that can aid medical institution in providing a better hand angle measurements for some identified movements. Three axis accelerometer sensors which are placed on particular positons on hand are used to observe the hand movements and then the results are visually presented to analyze the hand conditions. The hand movements can be further used to be characterized either on soft, medium or hard motions as these aspects are influential to realize real-time health monitoring system especially for elderly person.